Metastatic Pheochromocytoma Diagnosed with 131I-MIBG SPECT/CT Imaging in a Patient with Pathogenic VHL Mutation - Kousik Vankadari; Raman Boddula; Aditya Gajanan Hegde; Chimutai Chinte (World Journal of Nuclear Medicine)
Pheochromocytoma is a rare catecholamine secreting neuroendocrine tumor arising from chromaffin cells of adrenal medulla with approximate prevalence of 0.1 to 0.6% in patients suffering from hypertension. Hypertensive control followed by surgical resection remains the primary treatment of choice. Although it is considered a slow growing benign tumor, it rarely leads to recurrence of tumor in the lymph nodes, liver, and lungs. Association of benign pheochromocytoma with familial or de novo Von Hippel-Lindau (VHL) mutations is well reported in literature. Here, we report a case of metastatic pheochromocytoma arising from commonly seen benign VHL mutation.